Development of an Albumin-Based PSMA Probe With Prolonged Half-Life - Liu, Teli; Liu, Chen; Ren, Yanan; Guo, Xiaoyi; Jiang, Jinquan; Xie, Qing; Xia, Lei; Wang, Feng; Zhu, Hua; Yang, Zhi (Frontiers in Molecular Biosciences, 2020)
Prostate-specific membrane antigen (PSMA) is an attractive target for the diagnosis and therapy of prostate cancer as it is specifically overexpressed in prostate cancer cells. Improving the circulation of radioligands in the blood is considered as an effective strategy that can improve tumor burden, which benefits detection of small lesions and improves the effect of PSMA radioligand therapy (PRLT). In this study, we introduced maleimidopropionic acid (MPA) to a PSMA-targeted tracer and developed Al18F-PSMA-CM, which targets human serum albumin (HSA) binding and PSMA. Al18F-PSMA-CM is evaluated in vitro and in vivo for stability, PSMA specificity, and biodistribution in 22Rv1 tumor-bearing mice. Al18F-PSMA-CM was prepared with a radiochemical purity of >99% and specific activity of 11.22–18.70 MBq/nmol. Al18F-PSMA-CM was stable in vitro and in vivo and prolonged circulation in blood with a binding ratio of 47 ± 3.2% and Kd value of 3.08 ± 0.45 nM to HSA. The uptake of Al18F-PSMA-CM in PSMA(+) 22Rv1 cells was increased in 2 h, and the uptake was blocked by a PSMA inhibitor, ZJ-43. The Kd value of Al18F-PSMA-CM to PSMA was 8.46 ± 0.24 nM. Al18F-PSMA-CM was accumulated in kidneys and 22Rv1 tumors [74.76 ± 15.42 and 6.16 ± 0.74 ID%/g at 2 h post injection (p.i.)], which were decreased by −80.0 and −84.3% when co-injected with ZJ-43. Al18F-PSMA-CM showed high PSMA specificity and accumulated in 22Rv1 tumors with increasing uptake in 4 h. MPA moiety showed the ability to prolong the half-life of tracers, and the MPA-conjugated tracer showed the potential to improve tumor uptake. MPA may be a choice to develop radiopharmaceuticals for PRLT of prostate cancer.